Sustainable Food Practices in Hotel Operations: Challenges and Opportunities for Green Hospitality - Latip, Khairul Nisak Abd; Shaari, Siti Fitrika Nora (Tropical Scientific Journal, 2026)
Objective: The purpose of this paper is to examine sustainable food practices in hotel operations across Southeast Asia with particular attention to Malaysia and to explore the challenges and opportunities that influence their successful implementation, aiming to contribute insights into the development of green hospitality. Research Method: This study adopts a qualitative literature review approach, drawing evidence from peer-reviewed journal articles, international industry reports, and global sustainability guidelines published between 2010 and 2025. A thematic analysis was conducted to identify recurring practices, challenges, and opportunities. Findings: The review highlights that sustainable food practices in hotels primarily involve local and seasonal sourcing, efficient kitchen operations such as portion control and menu engineering, and systematic food waste management including donation and composting. The main challenges identified are high investment costs, inconsistent supply chains, and limited staff training. On the other hand, opportunities include long-term cost savings, improved brand image, higher guest satisfaction, and stronger community engagement. Originality: This paper contributes to the existing literature by synthesizing sustainable food practices within a framework of challenges and opportunities, while linking them to the triple bottom line of economic, environmental, and social outcomes. The conceptual perspective presented provides practical implications for hoteliers, policymakers, and educators seeking to align hospitality operations with sustainability goals. This paper not only synthesizes existing knowledge but also offers practical pathways for hotels, policymakers, and educators in Southeast Asia to strengthen sustainable hospitality frameworks